Dereplication of Lantana trifolia L. leaves and fruits by UFLC-DAD-(+)-ESI-MS/MS and its antifungal and cytotoxic activities - Valério, Gáveni Barbosa; Godinho, Camila Capel; Freitas, Thamires Rodrigues; Santiago, Mariana Brentini; Martins, Daniel Oliveira Silva [UNESP]; Jardim, Ana Carolina Gomes [UNESP]; Gobbo-Neto, Leonardo; Martins, Carlos Henrique Gomes; Cunha, Luís Carlos Scalon; Pilon, Alan Cesar [UNESP]; Coqueiro, Aline; Pivatto, Marcos; et al. (Springer Nature, 2023)
Introduction: Lantana trifolia L. (Verbenaceae) is a shrubby plant. In folk medicine, its leaves are used in the form of infusions and syrups to treat angina, coughs, and colds; they are also applied as tranquilizer. Previous studies have reported the antimicrobial potential of the compounds present in L. trifolia leaves. Objectives: To report the anti-Candida activities of the fractions obtained from the fruits and leaves of two L. trifolia specimens. Methods: The L. trifolia fractions were submitted to UFLC-DAD-(+)-ESI-MS/MS, and the data were analyzed by using multivariate statistical tools (PCA, PLS-DA) and spectral similarity analyses based on molecular networking, which aided dereplication of the bioactive compounds. Additionally, NMR analyses were performed to confirm the chemical structure of some of the major compounds in the fractions. Results: The ethyl acetate fractions presented MIC values lower than 100 µg mL–1 against the three Candida strains evaluated herein (C. albicans, C. tropicalis, and C. glabrata). Fractions FrPo AcOEt, FrPe AcOEt, and FrPe nBut had MIC values of 1.46, 2.93, and 2.93 µg mL–1 against C. glabrata, respectively. These values resembled the MIC value of amphotericin B, the positive control (0.5–1.0 µg mL–1), against this same strain. Cytotoxicity was measured and used to calculate the selectivity index. Conclusion: On the basis of our data, the most active fractions in the antifungal assay were more selective against C. glabrata than against non-infected cells. The analytical approach adopted here allowed us to annotate 29 compounds, nine of which were bioactive (PLS-DA results) and belong to the class of phenolic compounds.
Keywords: Anti-Candida; Lantana trifolia L; Molecular networking; Natural products